Structural and deleterious burdens and their effects on yield traits in foxtail millet domestication - Mengrui Du; Fan Zhang; Xu Wang; Tianhao Zhang; Xuanwen Yang; Yuting Liu; Yingchun Zhang; Ting Hou; Guizhou Hang; Xinyue Fang; Jiacui Li; Hui Xue; et al. (iScience)
Summary: Crop domestication typically accumulates structural and deleterious variants through genetic bottlenecks and selection hitchhiking. However, the structural and deleterious variant burden has not been investigated in the foxtail millet (Setaria italica). Integrating comparative genomics, pangenomics, population genetics, and quantitative genetics, we identified 6,713 gene gains and 2,802 losses during domestication, affecting flowering time and developmental processes. Population genetics of 333 wild and cultivated accessions revealed 25.76% and 40.40% reductions in structural and deleterious variant burdens in cultivars, potentially reflecting a dramatic loss of genetic diversity of the wild progenitor. Quantitative genetics detected genetic association of yield traits, and essential roles of deleterious and structural variants in the formation of yield traits. In general, this study highlights significant impacts of structural and deleterious variants on yield traits and provides valuable guidelines for molecular breeding of foxtail millet.